PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA MAN 1 PEKANBARU KELAS X PADA MATERI GERAK MELINGKAR - Yuli, Isma; Islami, Nur; Sudrajad, Hendar Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to describe and differentiate the learning motivation physics science between the implementation of cooperative learning type round table group with conventional learning group. This type of research is a quasi-experimental, with a nonequivalent control group design. Population in this research is all of X classes with 148 students. Meanwhile the samples are 30 students in X MIA 2 as control class and 28 students in X MIA 5 as experiment class. The instrument of data in this research is a ARCS motivation questionnaire. Analysis of the data in this study was a descriptive analysis that was used to view the category motivation to learning physics science with use n-gain formula. The analysis data shows n-gain of students motivation to learning physics science of the control class is 0.18 with low category and n-gain of the experiment class is 0.34 with medium category. Meanwhile n-gain for each indicator motivation to learning physics science of the control class is 0.19 with low category and n-gain of the experiment class is 0.35 with medium category. Therefore, it can be concluded that implementation of cooperative learning type round table can be used as an alternative in the learning process in the classroom X MAN 1 Pekanbaru.